Knowledge organization in traditional and electronic environment - Lasić-Lazić, Jadranka; Banek Zorica, Mihaela; Špiranec, Sonja Kesić-Mateljan, Bogdana (2005)
The Internet has already moved towards the next level (Internet 2) based on the WWW architecture known as the Semantic Web. In this new environment the Web will gradually be filled with content characterized by formally expressed semantics which will enable full automation of knowledge organization and its retrieval. Authors will talk about the type of network that incorporates a formal representation of relations between a document and its meaning (semantics) in order to make organization of information, as well as information services, fully functional through computer communication (m2m). Because the Semantic web is closely connected with the development of the so called ontologies, it will be explained and compared with traditional knowledge organization tools, like classification and thesaurus. Furthermore, the necessity of such tools in the context of the Semantic web will be shown.
Projekt MZOS
ENG